Endobronchial Lipomatous Hamartoma: An Incidental Finding in a Patient with Atrial Fibrillation—A Case Report - Friederike Schneider; Hauke Winter; Florian Schwarz; Manuel Niederhagen; Vivian Arias-Herrera; Eimo Martens; Stefan Kääb; Hans Theiss (Case Reports in Medicine)
Introduction. Lung hamartomas are the most common benign tumors of the lung. Typically, they are located in the peripheral lung, while an endobronchial localisation is rare. Case Presentation. We present a case with the rare diagnosis of an endobronchial hamartoma as incidental finding in a 69-year-old male, caucasian patient with atrial fibrillation. At first admission, the patient’s exertional dyspnea was caused by atrial fibrillation. Relapse of exertional dyspnea in the absence of arrhythmia was due to postobstructive pneumonia caused by an endobronchial hamartoma. Conclusion. Endobronchial tumors such as endobronchial lipoma or hamartoma should be considered as potential causes of exertional dyspnea and thus as differential diagnosis of atrial fibrillation. Although endobronchial hamartomas are benign, resection is recommended to prevent postobstructive lung damage.